Effectiveness of Rhizobacteria from Muting District (DMSJ 3) and Semangga District (DSK 3) in Increasing Rice Yield (Oryza Sativa L.) Under Drought Stress - Reynara Lapomi, Malvin; Ayu Kade Sutariati, Gusti; Corina Rakian, Tresjia (International Journal of Science, Technology & Management, 2025)
Drought is a climatic phenomenon that can significantly disrupt the growth and reduce the yield of rice plants. Inoculation of rhizobacteria can increase the yield of rice plants under drought stress conditions. The research was conducted at the Agrotechnology Laboratory of Agronomy Unit and Experimental Garden II of Faculty of Agriculture, Halu Oleo University, Kendari from October 2024 to January 2025. The treatments in this study were drought stress and rhizobacterial isolates. Drought stress treatment consisted of control (K0), 25% drought stress (K1), 50% drought stress (K2) and 75% drought stress (K3) while rhizobacterial treatment consisted of control (B0), isolate DMSJ 3 (B1) and isolate DSK 3 (B2). Each treatment was repeated 3 times, the treatment pots were arranged according to a split-plot design consisting of 5 polybags. Observational data were statistically analyzed using analysis of variance at the real level ? 0.05 and will be further tested with DMRT ? 0.05 if it shows a significant effect. The results showed that inoculation of rhizobacterial isolates DMSJ 3 and DSK 3 was able to increase plant yield under drought stress conditions characterized by an increase in the number of productive tillers, flag leaf area, flowering age, total grain per panicle, percentage of filled grain per panicle, 1000 grain weight, grain weight per panicle, yield and drought tolerance index. Isolates DMSJ 3 and DSK 3 have the same ability to increase yield and induce resistance of rice plants to drought stress conditions.